Stiffening Strategies: A 20-Year Review of Agricultural Journalist Experiences in the Publication-Reader-Advertiser Triad - Stephen Banning; Jim Evans; Owen Roberts; Karen Simon (Journal of Applied Communications, 2010)
This research examined relationships among agricultural journalists/editors, publishers of U. S. commercial farm periodicals and advertisers across a 20-year period, from 1988 to 2008. In particular, it focused on the journalists’ perceptions of influences on editorial content. Researchers used a contractualist model within the framework of social contract theory that features relationships based on mutual consent, pursuit of mutual benefits and mutual options for departure from the publication-reader-advertiser triad. They replicated studies of 1988 and 1998 among members of the American Agricultural Editors’ Association to permit a 20-year analysis of trends in perceptions and experiences. Findings revealed continuing concern among agricultural journalists about pressures on editorial content and integrity. They reported harm associated with advertising-related pressures, as well as with getting too close to those they cover. At the same time, results of this study revealed evidence of active, increasing resistance to such pressures and increased sensitivity to harm that may be associated with practices that compromise editorial coverage and content. Also, results of the 2008 survey showed evidence that advertisers may be taking steps to help protect the editorial independence of these agricultural journalists and their publications.
Keywords: Stiffening; Strategies; agricultural; journalists/editors; publishers; perceptions; advertisers; ethics-related caution